Peran Badan Kesatuan Bangsa dan Politik Provinsi Jawa Timur dalam Pemberdayaan Organisasi Kemasyarakatan Berbasis Kearifan Lokal melalui Seni Wayang - Rustiani Rustiani; Sapto Pramono; Sri Roekminiati (Politeknik Kampar, 2025)
This research seeks to examine the function of the East Java Provincial Agency for National Unity and Politics (Bakesbangpol) in enhancing community organizations via wayang art, highlighting aspects of public policy and administration grounded in local wisdom. The study utilized a qualitative case study approach. Data were gathered via in-depth interviews, participatory observation, and examination of policy documents and activity reports. Data analysis involved reduction, visualization, and conclusion formulation to uncover consistent trends in policy execution. The results show that Bakesbangpol functions as a regulator, as well as a facilitator, mediator, and catalyst. Empowerment initiatives are executed by enhancing organizational capabilities, promoting cross-sector collaboration, digitizing wayang art, and incorporating cultural values into education and local policies. These initiatives have enhanced social unity, boosted youth involvement, encouraged the creative sector, and solidified East Java’s cultural identity. The research showcases a blended framework of public policy that merges contemporary governance with heritage principles, resulting in flexible and enduring results. The uniqueness of this study is in presenting wayang art as a tool for community empowerment and a public policy approach to tackle modern social, political, and cultural issues.